Marginalization of Shamans in Reporting Gus Samsudin and The Red Magician on CNN.COM and OKEZONE.COM News Portals With Theo Van Leeuwen Analysis Model - Neina, Qurrota; Prasetyo Yuli Kurniawan; Leni Septiani (Jurnal Sastra Indonesia, 2024)
Social inequality in shaman associations in Indonesia has gained media attention. Shamanism is a popular profession in Indonesian society. This study aims to (1) describe the forms of actor partiality domination in the cnn.com and okezone news portals and (2) describe the forms of shaman marginalization in the cnn.com and okezone.com news portals. The subjects of this study are articles on the cnn.com and okezone.com news portals. At the same time, the object of this study is the strategy of exclusion and inclusion in the reporting of shaman figures. The data was collected using the documentation method in five articles on cnn.com and okezone.com. The data that met the criteria would be used. Therefore, this news is selected based on a purposive sampling technique. The data were then analyzed using Theo van Leeuwen's critical discourse analysis. The results show that (1) based on the statements in the media, it is known that shamans are already experiencing a shift in their position in society. The partiality of the shaman figure in reporting can be seen in the exclusion and inclusion strategies. Based on data, cnn.com is more in favor of shaman figures than okezone.com, and (2) this form of marginalization eventually pushed people's thinking and formed a new ideology. In a community in the past, shamans, who were described as intelligent people, were able to give trust to the community. However, at this time, shaman figures become news that is viewed negatively by the community.